Multi-drug resistance-1 (MDR-1) gene expression in MCF-7 cells after treated with doxorubicin-deoxyelephantopin combination and prediction of inhibitory activity against Pgp receptors with in silico - DANIEL, DANIEL; FRENGKI, FRENGKI; JALALUDDIN, MUHAMMAD; SARI, WAHYU EKA; ROSMAIDAR, ROSMAIDAR; HASRIATI, HASRIATI; ZAKIAH, NONI (Jurnal Natural, 2024)
Doxorubicin chemotherapy has been a strong focus in breast cancer research. Side effects, toxicity and resistance have been extensively studied. One proposed solution to these issues that its combination with deoxyelephantopin. Deoxyelephantopin is known to be toxic in many cancer cells but safe in normal cells. IC50 of each compound were determined by using a MTT assay, and the MDR-1 gene mRNA expression were determined by using qPCR method, while the interaction of doxorubicin in combination with deoxyelephantonin on Pgp receptor were predicted by using an in silico approach. The IC50 of deoxyelephantopin was found to be 11.2 g/mL, while IC50 of doxorubicin was 448 nM IC50 values showed a deoxyelephantopin-doxorubicin combination was able to reduce MDR-1 expression by 19% compared to doxorubicin and IC50 values indicated that the combination formula reduced the expression by 15% over doxorubicin alone. The affinity of doxorubicin and deoxyelephantopin is -12.16 kcal/mol and -9.51 kcal/mol, respectively, while the affinity of doxorubicin after combine with deoxyelephantopin decreases from -12,16 kcal/mol to -11,25 kcal/mol due to the release of one Leu 221 hydrogen bond. The combination of doxorubicin with deoxyelephantopin is able to reduce expression and suppress the function of the Pgp protein.